Moderate Alcohol Use and Mortality from Ischaemic Heart Disease: A Prospective Study in Older Chinese People - Schooling, C. Mary; Wenjie, Sun; Ho, Sai Yin; Chan, Wai Man; Tham, May Ked; Ho, Kin Sang; Leung, Gabriel M.; Lam, Tai Hing (PloS one, 2008)
Moderate alcohol use is generally associated with lower ischaemic heart disease (IHD) mortality but it is difficult to ascertain whether this is due to attributes of moderate alcohol users or the properties of alcohol itself. Evidence from populations with different patterns of alcohol use and IHD can provide crucial evidence. We assessed the association of moderate alcohol use with IHD mortality in older Chinese people from Hong Kong. We used Cox regression to determine whether moderate alcohol use was associated with IHD mortality in a prospective, population-based cohort study of all 56,167 attendees, aged 65 years or over, from July 1998 to December 2000 at all 18 Elderly Health Centers operated by the Department of Health in Hong Kong. After a median follow-up of 4.2 years, there were 406 (188 in men, 218 in women) deaths from IHD in 54,090 subjects (96.3% successful follow-up). Moderate alcohol use in men was not associated with IHD mortality adjusted only for age [Hazard Ratio, HR 1.01 (95% CI 0.55 to 1.84) compared with never drinkers] or additionally adjusted for socio-economic status and lifestyle. Almost all women were occasional drinkers and their current alcohol use was not significantly associated with IHD mortality [HR 0.88, (95% CI 0.51 to 1.53)]. Moderate alcohol use had no effect on IHD mortality in older Chinese men. Lack of replication of the usual protective effect of moderate alcohol use in a setting with a different pattern of alcohol use and IHD could be due to chance or could suggest that the protective effect of alcohol on IHD does not extend to all populations.